Academic Senate Minutes 2009-02-05 - Academic Senate:::::::::
Chair Report. Correspondence. Agenda amended and approved. Biology Curriculum Revision – First Reading. Special Report: Dean Leeder presentation on the Holocaust and Genocide Memorial Grove. Minutes of 12/4/08 and 12/18/08 approved. Faculty Eligible for Emeritus Status approved. Resolution on the CLA – First Reading. SSU Statement on Collegiality – First Reading. APC Progress Report on the Core Academic Priorities Report – Second Reading. Special Report: GE Program Review. Statewide Senator Report.